Dual Brønsted acidic-basic function immobilized on the 3D mesoporous polycalix [4]resorcinarene: As a highly recyclable catalyst for the synthesis of spiro acenaphthylene/indene heterocycles - Aref Mahmoudi Asl; Bahador Karami; Mahnaz Farahi; Zahra Karimi (Heliyon, 2024)
In this study, a novel dual Brønsted acidic-basic nano-scale porous organic polymer catalyst, PC4RA@SiPr-Pip-BuSO3H, was synthesized through various steps: preparation of a 3D network of polycalix, modification with (3-chloropropyl)-trimethoxysilane, then functionalization of polymer with piperazine and n-butyl sulfonic acid under the provided conditions. The catalyst characterization was performed by FT-IR, TGA, EDS, elemental mapping, PXRD, TEM, and FE-SEM analyses, confirming high chemical stability, activity, recoverability, and excellent covalent anchoring of functional groups. So, the designed catalyst was utilized for preparing spiro-acenaphthylene and amino-spiroindene heterocycles, providing good performance with a high yield of the corresponding products. Accordingly, this catalyst can be used in different organic transformations. Necessary experiments were conducted for the recyclability test of the polymeric catalyst, and the results showed the PC4RA@SiPr-Pip-BuSO3H catalyst can be reused 10 times without any decrease in its activity or quality with excellent stability. The structure of resultant spiro heterocycles was confirmed using 1H NMR, 13C NMR, and FT-IR.